Blood cytokine concentrations in pediatric patients with anaplastic lymphoma kinase-positive anaplastic large cell lymphoma - Knörr, Fabian; Damm-Welk, Christine; Ruf, Stephanie; Singh, Vijay Kumar; Zimmermann, Martin; Reiter, Alfred; Woessmann, Wilhelm; Justus Liebig University Giessen (My University, 2018)
Patients with anaplastic lymphoma kinase-positive anaplastic large cell lymphoma often present with B-symptoms or hemophagocytosis and generate an anti-tumor immune response. Specific serum cytokine levels or profiles may reflect the tumor burden, non-specific immune stimulation by the tumor or differences in the strength of the patients anti-lymphoma immunity. We systematically correlated pretreatment concentrations of 25 cytokines with clinical and biological characteristics in a well-characterized cohort of 119 uniformly treated pediatric patients with anaplastic large cell lymphoma. Fifteen patients with anaplastic large cell lymphoma in remission and 11 patients with low-stage B-cell lymphoma served as controls. Concentrations of interleukin-9, interleukin-10, interleukin-17a, hepatocyte growth factor, soluble interleukin-2 receptor, and soluble CD30 were significantly higher in initial sera of patients than in the sera of subjects from both control groups, indicating an anaplastic large cell lymphoma-type cytokine signature. The levels of interleukin-6, interferon-gamma, interferon gamma-induced protein, and soluble interleukin-2 receptor correlated with the stage, initial general condition, minimal disseminated disease, anaplastic lymphoma kinase-antibody titers, and the risk of relapse among patients with anaplastic lymphoma kinase-positive anaplastic large cell lymphoma. Only interleukin-6 showed an independent prognostic value in multivariate analyses. Pretreatment cytokine profiles in patients with anaplastic large cell lymphoma reflect a tumor signature as well as tumor burden and also differences in the strength of the patients immune response.
Keywords: ddc:610